2013
DOI: 10.1039/c3fd00061c
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-coil driven membrane fusion: zipper-like vs. non-zipper-like peptide orientation

Abstract: Membrane fusion plays a central role in biological processes such as neurotransmission and exocytosis. An important class of proteins that induce membrane fusion are called SNARE (soluble N-ethyl malemeide sensitive factor attachment protein receptors) proteins. To induce membrane fusion, two SNARE proteins embedded in opposing membranes form a four-helix coiled-coil motif together with a third, cytoplasmic, SNARE protein. Coiled-coil formation brings the two membranes into close proximity allowing fusion to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Fig. 2 A displays the change of fluorescence intensity upon varying the lipid to peptide ratio by addition of vesicles of the composition DOPC:DOPE:cholesterol (molar ratio: 2:1:1), as used in recent vesicle fusion studies (5)(6)(7)(8)(9)(10)16,44,45). For comparative purposes, the total concentration of the tryptophan bearing peptide (X*, X ¼ K or E, respectively) was kept constant.…”
Section: Membrane Binding Of K Before and After Vesicle Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 A displays the change of fluorescence intensity upon varying the lipid to peptide ratio by addition of vesicles of the composition DOPC:DOPE:cholesterol (molar ratio: 2:1:1), as used in recent vesicle fusion studies (5)(6)(7)(8)(9)(10)16,44,45). For comparative purposes, the total concentration of the tryptophan bearing peptide (X*, X ¼ K or E, respectively) was kept constant.…”
Section: Membrane Binding Of K Before and After Vesicle Dockingmentioning
confidence: 99%
“…Therefore for further quenching measurements at constant lipid concentrations, this ratio was chosen. For measurements with LPE* and LPK*, a ratio of 100:1 was chosen because this reflects the conditions of typical vesicle fusion experiments (5)(6)(7)(8)(9)(10)16,44,45).…”
Section: Membrane Binding Of K Before and After Vesicle Dockingmentioning
confidence: 99%
“…[1][2][3] Amongst those, membrane tethered coiled-coil forming lipopeptides whose design has been inspired by natural SNARE (soluble NSF attachment protein receptor) proteins have been examined extensively in different studies because they were shown to trigger specific and leakage free full fusion of vesicles. 1,[4][5][6][7][8][9][10][11][12][13][14][15] The lipopeptides used here consist of a cholesterol lipid anchor connected via a polyethylene glycol (PEG 12 ) spacer to the peptide moieties (lipopeptides CPE, CPK; Chart 1A). The peptide recognition unit is made of two hetero coiled-coil forming peptides called E: (EIAALEK) 3 -NH 2 and K: (KIAALKE) 3 -NH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…CC-K/E is known to induce efficient and targeted membrane fusion when both peptides are modied with a lipid anchor and incorporated into liposome membranes. 20,22,23,26 These fusogenic constructs comprise three distinct segments: the peptide segment, which serves as the recognition unit; a hydrophobic cholesterol anchor, which enables the construct to be secured in a liposome membrane, and; a hydrophilic linker, which is thought to be crucial for allowing force transduction and therefore helping to facilitate fusion in natural SNARE systems. 6,50,51 In addition to the linking region being crucial for fusion, it is postulated that the peptides need to be in a parallel orientation, as their 'zippering' from one terminus to the other as they fold provides the force that draws the two membranes close together and induces them to fuse.…”
Section: Fusion Studiesmentioning
confidence: 99%
“…[20][21][22][23] It has been postulated that, for fusion to occur, the fusogens need to be aligned in a parallel orientation allowing them to 'zipper' up from their distal N-termini to their membraneproximal C-termini, generating an inward force that pulls the two membranes together and forces them to fuse. 24,25 To probe this 'zipper' hypothesis, peptides that are anchored into the membrane at opposing termini, 26 or peptides that have an antiparallel orientation can be used, Scheme 1. Previous studies have shown that both antiparallel SNARE derivatives and short antiparallel coiled coils cannot induce fusion.…”
Section: Introductionmentioning
confidence: 99%